Perinatal outcomes of pregnant women having SARS-CoV-2 infection - Sevcan Arzu Arinkan; Ezgi Ceren Dallı Alper; Gunes Topcu; Murat Muhcu (Elsevier, 2021)
Objectives: Aim of this study is to evaluate the prognosis of pregnant women having SARS-CoV-2 infection and investigate whether there was a difference in perinatal outcomes between pregnant women who had SARS-CoV-2 infection and those who did not. Materials and methods: This prospective observational study was conducted with 116 singleton pregnancies. Cases enrolling in the study were divided into two groups. While those in the first group had a history of SARS-CoV-2 infection (n = 46) the second group consisted of healthy pregnant women (n = 70). Results: Emergency Cesarean section was performed on three SARS-CoV-2 infected pregnancies (30, 33 and 34 gestational weeks). Intensive care unit admission was required for all three cases after delivery and two of them died. Among the pregnancies that had an infection in the third trimester, 71.4% (n = 20) of them had delivery in 14 days after diagnosis and 17.4% (n = 8) of their newborns were followed up at newborn intensive care unit. Overall, only one newborn had a positive swab test result for SARS-CoV-2. There was no statistically significant difference between groups regarding their delivery week (37.02 ± 5.85 vs 38.5 ± 2.33). Similarly, there was no significant difference between groups, concerning mean age, parity, and birth weight (P = 0.707, P = 0.092, P = 0.334; P < 0.05). Furthermore, the difference between SARS-CoV-2 infected pregnancies that were followed up as inpatient or outpatient with respect to the delivery week and birth weight was not significant (p > 0.05). Also, APGAR 5 scores of hospitalized women (9.3 ± 1.1) were found to be lower than the outpatient group (9.8 ± 0.8) (P = 0.043; p < 0.05). Conclusion: No significant difference was detected between groups in terms of the delivery week, birth weight, and APGAR scores. The inpatient group was found to have lower APGAR 5 scores.